Understanding College Pathways for Rural Appalachians in Tennessee - Potter, Darek; Simone, Kinsey; Isbell, Janet Kesterson; Hinkel, Shawn (International Journal of Qualitative Research, 2024)
Rural students encounter unique obstacles as they pursue higher education. Knowledge of such obstacles can be valuable to stakeholders seeking to prepare, recruit, and retain rural students. This interpretive case study sought to understand postsecondary college pathways from the perspectives of nine participants who attended rural high schools in Appalachia, specifically the Upper Cumberland region of Tennessee, and earned a postsecondary degree. Through analysis of face-to-face interviews, researchers found that family and teachers were significant in rural students’ guidance and academic success, yet most participants noted a lack of support from high school administrators and counselors. Some participants said their schools failed to prepare them for college, and most said they lacked study skills, yet most participants had access to dual credit, and all participants succeeded in college. Participants’ pride in their rural roots led most to return to their hometowns after college. The study demonstrates the need for better college and career counseling from rural students’ school leadership and for more diverse experiences while still in high school to help prepare rural students for college.